Synthesis, Characterization and in vitro Antifungal Screening of Manganese(II) and Copper(II) Complexes of Hexaaza [N6] Macrocyclic Ligand - Kumar, U.; Chandra, S. (Journal of Nepal Chemical Society, 2010)
New manganese(II) and copper(II) complexes of 12-membered macrocyclic Schiff base ligand containing thiosemicarbazone moiety have been prepared of general composition [MLX2] where M = Mn(II) or Cu(II), L = 3,4,9,10–tetra-2-furanyl-1,2,5,6,8,11- hexaazacyclododeca-7,12-dithione-2,4,8,10–tetraene, X = Cl-, NO3- and NCS-. The complexes have been characterized by elemental analysis, molar conductance, magnetic susceptibility measurements and spectral (IR, electronic, EPR and mass) analyses. The IR spectra of complexes suggested that ligand is coordinated to the metal ion through imine nitrogen atoms. On the basis of spectral studies, an octahedral and tetragonal geometry has been assigned for Mn(II) and Cu(II) complexes, respectively. EPR spectra of polycrystalline Mn(II) complexes gave an isotropic signal with g value centered around free electron g value. EPR spectra of Mn(II) complexes in DMSO showed hyperfine splitting containing six lines, whereas EPR spectra of polycrystatalline Cu(II) complexes showed anisotropic signal. Conductivity measurements support the non electrolytic nature of the complexes. Magnetic moment data suggest that reported complexes are paramagnetic and of high spin type. All the examined complexes have also been tested in vitro against a number of pathogenic fungi. Results indicated that the complexes exhibited good antifungal activities. Keywords: Macrocyclic, octahedral, antifungal, tetragonal, anisotropic. DOI: 10.3126/jncs.v25i0.3284 Journal of Nepal Chemical Society Volume 25, 2010 pp 46-52